PROMOTION OF THE AUTOLYSIS OF α-CHYMOTRYPSIN BY EVANS BLUE - Glazer, A. N. (1969)
Evans blue has been demonstrated to promote the autolysis of α-chymotrypsin at low dye-to-protein ratios in alkaline solution. This effect has been attributed to the stabilization of less tightly folded conformers of the protein by the dye. The effect is specific. Of 20 other strongly acidic dyes tested, only trypan red showed activity comparable to that of Evans blue. A general discussion of the influence of ligand binding on the stability of proteins is presented.